Sacred Waters and Environmental Virtue: A Comparative Study of Religious Rituals and Water Conservation Ethics - Fibry Jati Nugroho; Eko Sutrisno; Fahrizal S.Siagian (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study explores the intersection of sacred water rituals and ecological awareness, examining how religious practices related to water shape environmental virtues and promote water conservation efforts. Various religious traditions, including Islam, Christianity, Hinduism, and indigenous practices, treat water as a sacred resource, emphasizing its purity, sanctity, and the responsibility of humans to protect it. These rituals, such as Islamic ablution (wudhu), Christian baptism, and Hindu purification rites, not only serve spiritual purposes but also embody environmental ethics that encourage restraint, humility, and stewardship in the use of water. The study employs a comparative qualitative approach, integrating textual exegesis, ethnographic observations, and interviews with religious practitioners to analyze how different faith traditions frame water as sacred and how these frameworks translate into practical behaviors regarding water conservation. The findings reveal that religious water rituals contribute to an ecological self, fostering a deep respect for nature and a commitment to sustainable water use. However, challenges exist in reconciling traditional practices with modern water scarcity issues, especially in regions where water conservation is a critical concern. Despite these challenges, religious communities have the potential to leverage their ritual heritage to foster global awareness and action toward water conservation. Future research should explore interfaith collaborations in water conservation and investigate the impact of ritual practices on real-world water conservation behaviors. This study highlights the potential of sacred water rituals as powerful tools for promoting environmental stewardship and addressing global water challenges.